2016
DOI: 10.1371/journal.pone.0152282
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Recombinant Monoclonal Antibodies from Immunised Mice and Rabbits via Flow Cytometry and Sorting of Antigen-Specific IgG+ Memory B Cells

Abstract: Single B cell screening strategies, which avoid both hybridoma fusion and combinatorial display, have emerged as important technologies for efficiently sampling the natural antibody repertoire of immunized animals and humans. Having access to a range of methods to interrogate different B cell subsets provides an attractive option to ensure large and diverse panels of high quality antibody are produced. The generation of multiple antibodies and having the ability to find rare B cell clones producing IgG with un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
65
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(67 citation statements)
references
References 42 publications
0
65
2
Order By: Relevance
“…Previous studies of the porcine memory B cell, as well as that of the mouse, have shown that memory B cells develop and are maintained in several lymphoid structures (20,33). However, studies from other species would suggest that at least some component of memory is maintained in circulation (30,34,35). In this study, there was no evidence of nsp7-specific cells within key secondary lymphoid tissues after day 56, including day 118, 5 days after challenge.…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…Previous studies of the porcine memory B cell, as well as that of the mouse, have shown that memory B cells develop and are maintained in several lymphoid structures (20,33). However, studies from other species would suggest that at least some component of memory is maintained in circulation (30,34,35). In this study, there was no evidence of nsp7-specific cells within key secondary lymphoid tissues after day 56, including day 118, 5 days after challenge.…”
Section: Discussioncontrasting
confidence: 58%
“…The reason for the decline of these antigen specific populations in the lymph node can be attributed to the involution of germinal centers. The large increase in nsp7-specific B cells in the blood is likely due to the migration of nsp7-specific memory B cells out of the lymph nodes and into blood where these cells would be able to more actively search for specific antigen, as has been observed in other species with several pathogens (28)(29)(30). The delayed expansion of nsp7-specific B cells in the spleen is less clear.…”
Section: Discussionmentioning
confidence: 94%
“…Quantitative ranking of the binding of antibodies is frequently used to characterize candidate molecules and can be accomplished using ELISA, FACS, surface plasmon resonance systems (e.g., Biacore), and other methodologies. 7,8,11,15,26,[35][36][37][38][39][40] As of early 2019, the Beacon software was unable to generate quantitative values for fluorescent blooms. Despite the high-content imaging capabilities, this limited the built-in analysis to a binary (yes/no) result.…”
Section: Amgen Unpublished Data)mentioning
confidence: 99%
“…Moreover, we feel the overall workflow timeline can be executed even more rapidly. Successful VH and VL recovery and recombinant expression in 5-7 days have been demonstrated, 35,37,38 as have rapid immunization strategies. 42,43 Combining approaches such as these with the 1-day screening process of the NanOBlast method described here, complete antibody discovery workflows using antigen-experienced, affinity-matured ASCs could be executed in as little as 3-4 weeks.…”
Section: Amgen Unpublished Data)mentioning
confidence: 99%
“…Single B-cell isolation based on antigen capture by fluorescence-activated cell sorting, magnetic beads, solid-phase panning or hemolytic plaques followed by light- and heavy-chain cloning has also been applied to the generation of rabbit mAbs from peripheral B cells, 172, 173, 174, 175, 176 which does not require killing of the animal and allows for multiple sampling points from primary and secondary lymphoid tissues. 177 Antigen capture-driven bulk spleen B-cell isolation from immunized rabbits followed by light- and heavy-chain-encoding DNA amplification and their combinatorial assembly and expression in scFv–Fc or IgG format in mammalian cells has also been reported. 178 In the fluorescent foci method, plasma cells from rabbit bone marrow are identified by fluorescent microscopy, isolated and subjected to light- and heavy-chain-encoding DNA amplification and sequencing.…”
Section: Generation Of Rabbit Mabsmentioning
confidence: 99%